Implementation of Collaborative Governance in Managing BRIN's Research and Innovation Funding to Promote the Strengthening of Indonesia's Research Ecosystem - Erni Wibawati; Luh Putu Mahyuni (Eduvest - Journal of Universal Studies, 2024)
The study aims to provide an overview of the implementation of the funding scheme for research and innovation, as well as the involvement of stakeholders in the collaborative development of the research ecosystem and innovation. The study uses Ansell and Gash's collaborative governance theory, identifying stakeholders and analyzing stakeholder roles based on power and interests. (interest). The study employs descriptive research methods and qualitative data collection techniques. Data acquisition entails interviews, observations, and documentation from informants who are knowledgeable about these research issues. The findings demonstrate the fulfillment of Ansell and Gash's collaborative elements. Stakeholders in the research and innovation funding program consist of primary stakeholders, key stakeholders, and secondary stakeholders. The management of research and innovation funding involves a mapping of stakeholders, each with their own unique influences and interests. Stakeholders in the research and innovation funding program consist of primary stakeholders, key stakeholders, and secondary stakeholders. Key players include the Deputy for Research Facilitation and Innovation and the Deputy for Utilization Research and Innovation. Subjects that receive research and innovation funding are the Center for Research Collaboration and startups. Researchers from universities and research organizations wield significant influence as contest setters. The crowd includes the Deputy for Infrastructure Research and Innovation, the Directorate of Talent Management, the Inspectorate, and industry and company partners.